Poly[[tetra-μ3-acetato-hexa-μ2-acetato-diaqua- μ2-oxalato-tetra-praseodymium(III)] dihydrate] - Gutkowski, Karin (2011)
The title complex, {[Pr4(C2H3O 2)10(C2O4)(H2O)2] ·2H2O} n , was synthesized under hydro-thermal conditions from praseodymium acetate and the ionic liquid 1-butyl-3-methyl-imidazolium chloride via an in situ oxalate-ligand synthesis. The compound is a two-dimensional polymer and in the structure presents tightly bound planes parallel to (100), which are in turn linked into a three-dimensional network by hydrogen bonds involving both coordinated and solvent water mol-ecules. The oxalate anion lies across an inversion centre and acts as a bridge between pairs of Pr atoms within a tetra-nuclear segment of the polymer.